Inventory policy, accruals quality and information risk - Krishnan, Gopal V.; Srinidhi, Bin; Su, Lixin (Nancy) (Review of Accounting Studies, 2008)
This paper provides evidence consistent with firms with Last-in-first-out (LIFO) inventory policy being priced by the market as having lower information risk than First-in-first-out (FIFO) firms. Furthermore, the paper shows that this pricing differential is sustained after controlling for accruals quality, suggesting that the inventory policy signals some information risk characteristics that are not captured by accruals quality measure. We investigate the relation between inventory policy and accruals quality and find that accruals quality is systematically worse for FIFO firms than for LIFO firms after controlling for correlated omitted variables and known firm attributes. These findings complement the currently established relationship between the cost of capital, market pricing and accruals quality by focusing on the need for understanding the incremental effects of individual accounting policies.